Rock magnetic fingerprint of Mt Etna volcanic ash. Issue 2 (14th June 2022) - Vigliotti, Luigi; Bilardello, Dario; Winkler, Aldo; Del Carlo, Paola
SUMMARY: A detailed rock magnetic study was conducted on ash samples collected from different products erupted during explosive activity of Mount Etna, Italy, in order to test the use of magnetic properties as discriminating factors among them, and their explosive character in particular. Samples include tephra emplaced during the last 18 ka: the benmoreitic Plinian eruptions of the Pleistocene Ellittico activity from marine core ET97-70 (Ionian Sea) and the basaltic Holocene FG eruption (122 BC), the Strombolian/Phreatomagmatic/sub-Plinian eruptions (namely, the Holocene TV, FS, FL, ETP products and the 1990, 1998 eruptions) collected from the slope of the volcano, and the Recent explosive activity (lava fountains referred to as ' Ash Rich Jets and Plumes ', or ARJP) that occurred in the 2001–2002 period, related to flank eruptions. Mössbauer spectrometry informs that a single magnetic mineral dominates the three groups, which are characterized by variable magnetic grain sizes and composition. Detailed rock-magnetic investigations, ranging from low temperature to high temperature remanence and susceptibility experiments, indicate that the more explosive products of the Plinian eruptions and ARJP activity tephra, are characterized by oxidized Ti-rich titanomagnetites, with dominant Curie Temperatures between 230 and 330 °C. The FG and ARJP tephra are also characterized by contrasting, yet overall higher, coercivity distributions and higher magnetizations and susceptibilities, including below room temperature. In contrast, most of the Strombolian/sub-Plinian eruptions have a magnetic signature dominated by less coercive magnetite and/or Ti-poor titanomagnetite. Magnetic differences observed between the Late Pleistocene and Holocene FG Plinian eruptions can be attributed to the different composition of the former eruptions, which were fed by more evolved magmas, whereas geochemical variations characterizing the products erupted in the last few decades can be responsible for the differences between the Holocene and recent Strombolian/sub-Plinian products. Importantly, detailed magnetic investigation of sideromelane and tachylite clasts, the two end members of the juvenile fraction extracted from the ash of the most explosive products, determines that the tachylite fraction is responsible for the magnetic signature of the Plinian FG and ARJP tephra, and is attributed to the intense fragmentation that characterizes these activities, likely resulting from undercooling processes. Moreover, the abundant superparamagnetic grains associated with these eruptive styles are believed to represent the nanolite fraction responsible for the increasing viscosity of these magmas, and to be responsible for their explosive character. The distinctive magnetic properties that characterize the tachylite-bearing tephra, representative of the fragmentation process that distinguishes the most explosive activities, provides a useful magnetic tool that can complement traditional volcanological investigations.